Pengaruh Kompetensi Terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kota Cimahi - Marliana, Nova; Soesilo, Soesilo; Rukminingsih, Tini (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
One of the aspects that play an important and crucial role in the process of national development that is carried out quickly is infrastructure development. In addition, infrastructure also plays an important role in economic growth. To be able to realize this, the performance of employees has an important role. One component of improving employee performance in both government and private institutions is competence. So that it is necessary to develop human resources in order to improve employee performance, one of which is the PUPR Office in Cimahi City. This study aims to find out the effect of competence on performance in the PUPR Office of Cimahi City. In this study, the explanatory research method was used with a sample of 43 people. The analysis technique used is statistical analysis by means of regression, determination, correlation and hypothesis testing. The results of the study show that the competency variable has a positive and significant influence on employee performance with a determination value of 85.7%. The significance of the hypothesis test is 0.000 <0.05..